Pengaruh Latihan Range Of Motion terhadap Peningkatan Kemampuan Melakukan Activity Daily Living pada Penderita Pasca Stroke - Vier Nofrel; Mamat Lukman; Citra Windani Mambang Sari (Universitas Batanghari Jambi, 2020)
Stroke is a serious problem faced almost all over the world. The incidence of stroke varies between countries and places. Stroke ranks third largest in developed countries and is the third leading cause of death after heart disease and cancer. The disability due to stroke is generally higher than the mortality rate, globally 15 million people have a stroke each year, one third die and the rest experience permanent disability. Restoration of motor functions as a supporter of body movements in post-stroke clients is very important. This is because more than 85% of clients who suffer stroke have upper limb dysfunction. This Literature Study aims to analyze the effectiveness of Range of Motion (ROM) exercises on improving the ability of motion or independence of Activity Daily Living (ADL) in post-stroke clients. This study uses the literature review method by analyzing the results of previous studies. Search for articles was conducted on August 19 to August 31, 2019 through Pro-quest, Pubmed and Science Direct databases using the keywords Activity Daily Living AND Range of Motion AND Post Stroke, then article selection based on criterion of inclusion was carried out critical appraisal so that the relevant articles amounted 14 articles. From a number of studies conducted by previous researchers, it was found that there was a significant effect of Range of Motion training on increasing the ability of the stroke client's range of motion. The Range of Motion training program is effective in increasing the ability of the client's range of motion after a stroke so that it will have an impact on increasing the ability of clients to do daily living activities.